(3JMQjQ GdbhGYO GdefWbjI aj TQM GdTeSjIs - (3GdQGRj, GdbWH GdJMJGfj, eMeO Hf eMeO, J (B766 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Ef CHgi OQQ JfXe HHfjGf GdHjGf HYO abO WGd EdMGM GdeTJZdjf Ydj hGdeJQOOjf Edi Cf CTQM dge GdQSGdI GdTeSjIs
(3BNQgG (B:s
(3GdeMShSGJ cGf MceG UMjMG hEf Mce Ydi ZjQ GdeMShSGJ HEMcGegG cGf cGPHG cGdMce HCf cd ehLhO eTGQ Edjg hCf hQGA GdYGde aVGAs
(3aj Chdg fbhd aj GdefWb hagQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/38s
(3eYLe GdeDdajf (B3/642s
(3cTa GdXfhf (B2/ 1063s
(3TPQGJ GdPgH (B6/207s
Keywords: (3GdadSaI hGdefWbs